Analyzing Global University Rankings: Trends And Implications - Sardorbek Diyorov Husanboy o‘g‘li (Periodica Journal, 2024)
This article explores the close relationship between national development and the quality of education, particularly in the context of countries whose universities are ranked among the top 100 in the world. It highlights how the most developed countries— such as the United States, the United Kingdom, Switzerland, China, Germany, Canada, and Japan—also lead in terms of the number and rank of universities in global educational rankings. The study emphasizes that educational advancement is a critical driver of national progress, with each country’s ability to invest in and improve its educational infrastructure having a direct impact on its global economic and political standing. The article also highlights the implications for third world countries, where improving the education system could play a pivotal role in boosting national development and global influence.
Keywords: National development; educational advancement; global university rankings